CIS by TRANS - Rodovalho, Amara Moira (Revista Estudos Feministas, 2017)
Cis, trans: above all, metaphors. Cisjordan, region skirting the Jordan River. Cisplatin, Uruguay’s ancient name, region occupying one of the banks of the Prata River. Trans- Amazonian, that which crosses the Amazon; transatlantic, that which crosses the Atlantic. Cisalpine, transalpine. The geometric isomerism of Organic Chemistry, where “cis” are atoms that, when molecules are divided in half, remain on the same side, and “trans” those remaining on opposite sides. Even the Houaiss dictionary, presenting the cis etymology as “from the Latin preposition cis ‘below, on this side’ (in opposition to trans)”. And many other examples. Metaphors, always metaphors. Something that crosses, trespasses, goes through and something that remains always on the same side, skirting, not crossing, that avoids crossing, all in relation to a given line. Can we imagine the use of one of these terms without, immediately, referring to the other? From this rhetorical question, I dare to claim that medical discourse, by naming as “trans” our peculiar way of living, of claiming existence, has automatically named the other way, its way, non-trans, as “cis”, leaving to us only the task of thinking ways of making the two images proposed, something-that-crosses and something-that-avoids-crossing, translate themselves into more tangible meanings.